Poly(Ionic Liquid) Based Chemosensors for Detection of Basic Amino Acids in Aqueous Medium - Li, Xinjuan; Wang, Kai; Ma, Nana; Jia, Xianbin (Frontiers in Chemistry, 2017)
Naked-eye detection of amino acids (AA) in water is of great significance in the field of bioanalytical applications. Herein, polymerized ionic liquids (PILs) with controlled chain length structures were synthesized via reversible addition–fragmentation chain-transfer (RAFT) polymerization and post-quaternization approach. The AA recognition performance of PILs with different alkyl chain lengths and molecular weights was evaluated by naked-eye color change and ultraviolet-visible (UV–vis) spectral studies. These PILs were successfully used for highly sensitive and selective detection of Arg, Lys, and His in water. The recognition performance was improved effectively with increased molecular weight of PILs. The biosensitivity of the PILs in water was strongly dependent on their aggregation effect and polarization effect. Highly sensitive and selective detection of AA was successfully accomplished by introducing positively charged pyridinium moieties and controlled RAFT radical polymerization.